Increased physical activity reduces sleep disturbances in asthma: A randomized controlled trial. Issue 1 (6th September 2022) - Passos, Natalia Febrini; Freitas, Patricia D.; Carvalho‐Pinto, Regina Maria; Cukier, Alberto; Carvalho, Celso R. F.
Abstract: Background and objective: Individuals with asthma are more likely to develop sleep‐disordered breathing. Exercise training improves sleep; however, the effect of physical activity (PA) on improving sleep quality remains unknown. This study had two objectives: (i) to evaluate the effect of a behavioural intervention to increase physical activity in daily living (PADL) on sleep quality in adults with asthma; (ii) to verify the association between a change in sleep quality, quality of life, anxiety, depression and asthma symptoms. Methods: This randomized controlled clinical trial included adults physically inactive with asthma. Participants were randomized into the control (CG; n  = 25) and intervention groups (IG; n  = 24). IG was submitted to a behavioural intervention to increase PADL, and CG received the usual care. Pre‐ and post‐intervention assessments of sleep quality (by actigraphy and questionnaire), PADL level (by accelerometry), asthma control, health‐related quality of life and anxiety and depression levels were conducted. Results: Both groups were similar at baseline. After the intervention, IG increased daily steps and moderate to vigorous PA levels. IG also improved sleep efficiency and latency as well as increased asthma‐symptom‐free days compared to CG. In addition, a greater proportion of participants in the IG had improved sleep quality after the intervention. Lastly, IG presented clinical improvement in the asthma‐related quality of life questionnaire and a reduction in anxiety symptoms. Conclusion: Our results demonstrate that a behavioural intervention can increase PA, enhance behavioural sleep quality, efficiency and quality of life and reduce asthma and anxiety symptoms. Abstract : We evaluated the effect of increased physical activity in daily living (PADL) on sleep quality, quality of life and symptoms in adults with asthma and how improvement in sleep quality was associated with anxiety symptoms. Increased PADL improved sleep quality, quality of life, asthma and anxiety symptoms. Improved sleep quality was associated with better asthma control. See related Editorial